Gamma irradiation-induced variability in morpho-agronomic and oil quality traits of Mentha piperita L. (4th May 2021) - Prasad, Priyanka; Singh, Vagmi; Aftab, Nashra; Gupta, Akancha; Kishor, Ram; Kushwaha, Himanshu Kumar; Singh, Vivek; Verma, Ram Swaroop; Kumar, Birendra
Abstract: Purpose: To develop elite mutant in Mentha piperita having morphotype and oil content of Mentha arvensis, and oil quality of M. piperita . Materials and methods: The dormant runner of menthol rich genotype MPK-5 were subjected to different doses of γ- irradiation (10, 20, 30, 50, 70, 90, and 110 Gy) at a dose rate of 55 Gy/min to induce the genetic variability for herb and oil yield as well as oil quality. A wide spectrum of variability for agro-morphological traits, herb yield, and quality profile was observed among the mutants. Results: The developed and selected superior mutants viz. MPK-5(1) and MPK-5(3) have a mean herb yield potential of 23.923 and 21.503 Kg/9 m 2 ; mean oil yield of 92.953 and 80.047 ml/plot; mean menthol content of 69.012% and 69.160% with mean menthofuran content of 1.554% and 0.531%, respectively. Conclusions: Mutational breeding through γ- irradiation is considered complementary to the conventional breeding method, to broaden the spectrum of genetic variability. The developed and selected mutants namely viz. MPK-5(1) and MPK-5(3) identified as promising mutants, based on herb yield, oil yield, and essential oil quality, could be used as a parental line for exploitation in hybridization program/recombinant breeding.